Care-seeking behaviors for maternal and newborn illnesses among self-help group households in Uttar Pradesh, India - Kumudha Aruldas; Aastha Kant; P. S. Mohanan (BMC, 2017)
Abstract Background India has made large strides in reducing maternal mortality ratio and neonatal mortality rate, yet care-seeking behavior for appropriate care is still a challenge. We conducted a qualitative study to understand the process of recognition and care-seeking for maternal and newborn illnesses in rural India where a health intervention through women's self-help groups (SHG) to improve maternal and newborn health behaviors is implemented by a non-governmental organization, the Rajiv Gandhi Mahila Vikas Pariyojana. The study aimed to understand the process of recognition and care-seeking for maternal and newborn illnesses from SHG and non-SHG households in the intervention area. Methods Thirty-two illness narratives, 16 of maternal deaths and illness and 16 of newborn illnesses and deaths, were conducted. Women, their family members, and other caretakers who were present during the event of illness or death were included in the interviews. About 14 key informants, mainly frontline health workers (FLWs), were also interviewed. The interviews were conducted by two Population Council staff using a pre-tested guideline in Hindi. Results Our findings suggest that perceptions of causes of illness as "supernatural" or "medical" and the timing of onset of illness influence the pathway of care-seeking. Deep-rooted cultural beliefs and rituals guided care-seeking behavior and restricted new mothers and newborns' mobility for care-seeking. Though families described experience of postpartum hemorrhage as severe, they often considered it as "normal." When the onset of illness was during pregnancy, care was sought from health facilities. As the step of care for maternal illness, SHG households went to government facilities, and non-SHG households took home-based care. Home-based care was the first step of care for newborn illnesses for both SHG and non-SHG households; however, SHG households were prompt in seeking care outside of home, and non-SHG households delayed seeking care until symptoms were perceived to be severe. Conclusion Our findings indicate that care-seeking behavior for maternal and newborn morbidities could be improved by interventions through social platforms such as SHGs.